2020
DOI: 10.1016/j.cca.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Value of leukocytosis and elevated C-reactive protein in predicting severe coronavirus 2019 (COVID-19): A systematic review and meta-analysis

Abstract: Highlights Fever was associated with poor outcomes in patients with COVID-19. Leukocytosis was associated with severe disease. Leukopenia was associated with a better prognosis. CRP was associated with poor prognosis. Leuocytosis and CRP on arrival may predict severe COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
80
5
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 36 publications
9
80
5
4
Order By: Relevance
“…In this cohort of COVID-19 patients, some of the factors independently associated with of NIV failure were in line with those previously reported for other forms of acute hypoxemic respiratory failure 5,27 , like age and PaO 2 /FiO 2 , while others appear more specific of COVID 19, like serum levels of C-reactive protein 28 or platelet counts 29 , likely indicating an hyperinflammatory status or a progression towards multiple organ failure. Concerning the PaO 2 /FiO 2 ratio, the threshold value of 150 mmHg was highly predictive of NIV outcome, and, albeit this is still a speculation, it could probably be used as a simple criterion to decide which patients should undergo early intubation.…”
Section: Discussionsupporting
confidence: 90%
“…In this cohort of COVID-19 patients, some of the factors independently associated with of NIV failure were in line with those previously reported for other forms of acute hypoxemic respiratory failure 5,27 , like age and PaO 2 /FiO 2 , while others appear more specific of COVID 19, like serum levels of C-reactive protein 28 or platelet counts 29 , likely indicating an hyperinflammatory status or a progression towards multiple organ failure. Concerning the PaO 2 /FiO 2 ratio, the threshold value of 150 mmHg was highly predictive of NIV outcome, and, albeit this is still a speculation, it could probably be used as a simple criterion to decide which patients should undergo early intubation.…”
Section: Discussionsupporting
confidence: 90%
“…One of the most important laboratory parameters studied was WBC, which on average showed mild leukocytosis in patients, as previously found by studies (35,37,39). However, some studies have found leukopenia to be a more common finding in patients (36).…”
Section: Discussionsupporting
confidence: 62%
“…Temperature above 38°5 C at admission was also associated with a poor outcome in our cohort. We studied this variable, already described as a prognostic factor in COVID-19 (16,17), and especially as hyponatremia may be associated with fever. We found signi cant association between these two variables, but after multivariate analysis, only hyponatremia remains an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%